OBITUARY – REMEMBERING ANN LEVETT, 1936-2006 - Wilbraham, Lindy; Swartz, Sally (PINS-Psychology in Society, 2025)
Ann Levett died at her home in Cape Town in June 2006, aged 70 years. In a life well lived through a variety of different contexts and performances as intellectual, lecturer, supervisor, colleague, therapist, gender activist and human being, she indelibly inscribed the lives of many others. She had a 20-year association with the University of Cape Town, from which she retired as Associate Professor in 1996, honoured for her contribution to women and to feminist scholarship. She was Director of the Child Guidance Clinic at UCT between 1990-1992, where she oversaw the professional training of clinical psychologists. She also served on various committees as member of the Professional Board for Psychology (HPCSA) between 1994-1999. From 1996, she had worked in fulltime psychotherapeutic practice, with a powerful presence in the Cape Town psychoanalytic community as supervisor and mentor.